2016
DOI: 10.1155/2016/6987636
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Complementary and Alternative Medicine Use among Hypertensive Patients in Gondar Town, Ethiopia

Abstract: Background. Complementary and alternative medicine (CAM) therapies are being widely used by hypertensive patients worldwide. However, evidences regarding CAM use by hypertensive patients in Ethiopia are limited. This study aimed at assessing prevalence and correlates of CAM use among hypertensive patients attending ambulatory clinic at Gondar University Referral Hospital (GURH), Ethiopia. Methods. A cross-sectional study was employed on 423 patients visiting GURH. Descriptive statistics and bivariate and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 23 publications
5
42
1
Order By: Relevance
“…All ≥18 years old adult patients diagnosed with T2DM for at least 1 year prior to recruitment were taken as our source populations, while those patients who visited diabetes illness follow-up care clinic of UOGCSH to check blood sugar and refill medications during the data collection period were considered as a study population. Single population proportion formula was used with the assumption of 95% confidence interval, 5% margin of error, 72.3% prevalence [ 15 17 ] of herbal medicine use and 5% contingency for possible non-respondents. Considering the above points, the final sample size was determined to be 408.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All ≥18 years old adult patients diagnosed with T2DM for at least 1 year prior to recruitment were taken as our source populations, while those patients who visited diabetes illness follow-up care clinic of UOGCSH to check blood sugar and refill medications during the data collection period were considered as a study population. Single population proportion formula was used with the assumption of 95% confidence interval, 5% margin of error, 72.3% prevalence [ 15 17 ] of herbal medicine use and 5% contingency for possible non-respondents. Considering the above points, the final sample size was determined to be 408.…”
Section: Methodsmentioning
confidence: 99%
“…Those collectors were properly trained on the instrument and ways of approaching the patients. The questionnaire was prepared via appropriate modification of items in previously used instruments regarding herbal medicine use by T2DM patients [ 12 , 16 , 17 ] and items were thoroughly reviewed for relevance by all the authors. The questionnaire, first prepared in English, was then translated to Amharic language (local language) and back to English so as to ensure that the translated version gives the proper meaning.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…97 TCAM users among patients with HIV/AIDS Patients with HIV/AIDS who identified as a TCAM user in a number of studies across Sub-Saharan Africa were more likely to be female, 21 168 178-180 not married, 180 181 of low socioeconomic status, 21 180 younger (<39 years), 25 179 180 unemployed, 180 181 educated, 21 25 from a rural area 21 53 and of Christian religious denomination. 180 TCAM users among patients with hypertension and diabetes A review of the literature indicates that patients with hypertension who are male, 33 39 46 of low income level, 33 39 less educated, 33 older 106 and reside in rural area 33 are more likely to be TCAM users. A Ugandan study did not BMJ Global Health find any significant association between the sociodemographic profile of patients with hypertension and TCAM use.…”
Section: Prevalence Of Concurrent Use Of Tcam and Allopathic Medicinesmentioning
confidence: 99%
“…A similar finding was reported in a population-based study in Ethiopia. 49 Also, lack of patient belief in the safety and efficacy of TCAM was identified as a barrier to TCAM use in studies conducted among patients with hypertension, 33 pregnant women 88 and patients with various health conditions, 192 as well as in the general population. 49 In addition, two population-based studies 48 189 and a subhealth study 192 reported that respondents were reluctant to use traditional medical care due to the perceived demonic nature of TCAM.…”
Section: Tcam Users Seeking Infertility Carementioning
confidence: 99%